Odpowiedzi

2010-03-04T11:32:36+01:00
^ oznacza do kwadratu

(a+b)(3a+3b+2)+(2a+b)²=
=3a^+3ab+2a+3ab+3b^+2b-4a^+4ab+b^=
=7a^+2a+10ab+4b^+2b

(x+3b-5)(3x+3y)+(3x+2y-1)(x+3y)=
=x3^+9xb-15x+3xy+9yb-15y+3x^+9xy+2xy+6y^-x-3y=
=6x^+9xb-16x+6y^+14xy+9yb-18y

2(2+3b-5)(a+b-3)-(a+b)²=
=4a+4b-12+6ab+6b^-18b-10a-10b+30-a^-2ab-b^=
=-a^-6a+4ab+5b^-24b+18

3(2x+3y)(3x-2y)+(3x+4)²+(3x-3y-2)(x+y)=
=3(6x^-4xy+9xy-6y^)+(9x^+24x+16)+(3x^-3xy-2x+3xy-3y^-2y)=
=18x^+15xy-18y^+9x^+24x+16+3x^-2x-3y^-2y=
=30x^+15xy+22x-21y^-2y+16